EFEKTIVITAS PENGELOLAAN PEMBELAJARAN MYOB ACCOUNTING BERBASIS WEBLOG DI SMK N 1 SRAGEN - Khozanah, Hindun; Sutama, Sutama; Fuadi, Djalal (Universitas Muhammadiyah Surakarta, 2019)
This study aims to examine the effectiveness of the development of weblog-based MYOB Accounting learning management at SMK N 1 Sragen. This research is an R&D research. The development model used is Hannafin and Peck Model, with the stages of needs analysis, design, development and implementation. Data collection methods include interviews, questionnaires, observations, and documentation. Then the data were analyzed with descriptive analysis techniques, t test and gain test. The findings in this study are the significance value of the t-count using a weblog of 29.136 and the t-count of the lecture method of 15,581. This conclusions that t count weblog is greater than t count lecture, meaning that the effectiveness of the experimental class using the weblog is better than the control class using the lecture method. The results of the study using the N Gain test also obtained the value of the N Gain percent of the control class was 48.98, while the N Gain percent value of the experimental class was 67.33. The conclusion is learning in the experimental class using weblogs is more effective than the control class using the lecture method.